Production of Pravastatin by Filamentous Fungi Isolated from Soil - Emine, Seydametova (2013)
Pravastatin is a clinically useful cholesterol-lowering agent, selectively inhibiting 3-hydroxy-3-methylglutaryl-coenzyme A reductase, the regulatory enzyme in cholesterol biosynthesis. Currently, industrial production of this statin is based on a two-step fermentation process: the initial production of compactin and its subsequent biotransformation to pravastatin. The development of a one-step fermentation process using pravastatin-producing microfungi may be a commercially attractive approach. To facilitate this, isolation of novel fungal strains from different natural sources and their screening for pravastatin production is required. Soil being a reservoir for a wide variety of filamentous fungi has been recognized for a long time. In this study, 54 fungal cultures were obtained from soil samples collected in Pahang State (Malaysia). Isolates were cultivated in submerged fermentation and tested for their ability to produce pravastatin using high-performance liquid chromatography. Five selected pravastatin producers were identified to species level using cultural and morphological characteristics, physiological and biochemical tests, and molecular techniques. Screening of the important variables affecting pravastatin production by the best of these producers was initially carried out using 27-3 fractional factorial design and these selected variables were then optimized using rotatable central composite design. Kinetic studies of substrate uptake, fungal growth and pravastatin production in shake flask culture under optimized conditions were also conducted. Among 25 Penicillium isolates that were capable of producing pravastatin directly by fermentation, only five (ESF2M, ESF19M, ESF20P, ESF21P, and ESF26P) did so in relatively high concentrations, with Penicillium sp. ESF21P being the most active pravastatin producer, achieving a concentration of 196.83 mg/L. Fungal identification methods used in this study confirmed that the isolates Penicillium sp. ESF2M and ESF19M are referable to Penicillium citrinum, Penicillium sp. ESF20P and ESF26P were most closely related to Penicillium janthinellum, and Penicillium sp. ESF21P showed the highest homology with Eupenicillium brefeldianum. All sequence data from this study have been deposited in the GenBank database. A maximum concentration of 234.36 mg/L of pravastatin was produced by E. brefeldianum ESF21P under the optimized conditions suggested by the Design-Expert 6.0.8 software. Pravastatin fermentation using this fungus showed the typical kinetics of a secondary metabolite, with maximum yield obtained after about 288 h of fermentation.